PREVALENCE OF MULTI-DRUG RESISTANT TUBERCULOSIS AND ITS CORRELATION WITH RENAL COMPLICATIONS AND COMMUNITY PRACTICES - Muhammad Imran Ullah; Sumbul Naseem; Umar Alim; Muhammad Shaukat; Juneda Sarfraz; Zubeda Irshad (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: To determine the prevalence of MDR-TB and its association with renal complications and community practices in patients presenting to Gomal Medical College and its affiliated hospital.Methods: A descriptive cross-sectional study was conducted from January 2024 to January 2025, enrolling 72 microbiologically confirmed TB patients through consecutive sampling. Demographic and clinical data were collected using a structured proforma. GeneXpert and sputum smear results were recorded to confirm rifampicin resistance. Renal function was assessed using serum creatinine, blood urea nitrogen, and urinalysis. Community practices were evaluated through structured interviews. Data were analyzed in SPSS version 26, using chi-square tests to assess associations. A p-value